2013
DOI: 10.1167/iovs.12-10876
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Cx3cr1 Deficiency on Retinal Microglia in theIns2AkitaDiabetic Mouse

Abstract: PURPOSE. Diabetic retinopathy (DR) is a major cause of visual impairment in developed countries. While DR has been described classically as a microvascular disease, recent evidence suggests that changes to retinal microglia are an early feature of retinopathy. In our study, we assessed changes in microglial distribution and morphology in vivo and ex vivo in a mouse model of non-proliferative DR, and further examined effects of age and the absence of the functional chemokine receptor Cx 3 cr1 on the progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 56 publications
2
40
2
Order By: Relevance
“…Though diverse descriptions of layer separation have been shown by other groups with different investigative methods (Santos et al, 2008, Bosco et al, 2011, Kezic et al, 2013, Choe et al, 2014, microglia were found, in the present study, to be mainly located in three separate layers by epifluorescence microscopy on retinal flat mounts: the RGC layer (GCL, including the nerve fiber layer), inner plexiform layer (IPL), and outer plexiform layer (OPL). Studies have shown that the most obvious microglial proliferation is detected in the GCL after ON transection, whereas microglia in the OPL remain undisturbed (Garcia-Valenzuela et al, 2005).…”
Section: Quantitative and Morphological Evaluation Of Microgliacontrasting
confidence: 49%
“…Though diverse descriptions of layer separation have been shown by other groups with different investigative methods (Santos et al, 2008, Bosco et al, 2011, Kezic et al, 2013, Choe et al, 2014, microglia were found, in the present study, to be mainly located in three separate layers by epifluorescence microscopy on retinal flat mounts: the RGC layer (GCL, including the nerve fiber layer), inner plexiform layer (IPL), and outer plexiform layer (OPL). Studies have shown that the most obvious microglial proliferation is detected in the GCL after ON transection, whereas microglia in the OPL remain undisturbed (Garcia-Valenzuela et al, 2005).…”
Section: Quantitative and Morphological Evaluation Of Microgliacontrasting
confidence: 49%
“…In the optic nerve, microglia ramifications appear to be orientated along the fibres. This orientation is disorganized in an experimental model of diabetes , and the distribution and organization of microglia within the retinal layers is altered in a variety of pathological states, when changes in cell shape can be observed Kezic et al, 2013). Moreover, when RGCs are labelled with a retrograde vital fluorescent dye in an experimental axotomy, microglia containing RGC debris can be detected months after the injection of marker, indicating both the phagocytotic capacity of microglia and their relative longevity (Thanos et al, 1994).…”
Section: Origin Morphology and Distribution Of Microgliamentioning
confidence: 99%
“…In fact, most recent in situ analyses of ramified and reactive retinal microglia rely on Iba1 staining [26][27][28][29][30] as the marker allows consistent and reliable staining of microglia somata and their processes in a broad spectrum of different activation phenotypes [31][32][33] . In general, a combined in situ analysis of retinal microglia using sections and flat mounts as presented in our protocol is recommended.…”
Section: Development Of the Protocolmentioning
confidence: 99%